Cultivating Employees Using Maslow's Hierarchy of Needs - Stewart, Carol; Nodoushani, Omid; Stumpf, Jason (Competition Forum, 2018)
Stress caused by climates of fear in the workplace is sapping employee decision-making and causing conflict in the workplace. While hard to quantify, it is easy to understand why intelligent and engaged employees are the ideal: there are fewer mistakes and higher productivity. The primary metric used to frame the reasons for motivation is Maslow's Hierarchy of Needs. It is also vitally important to understand the power balance between employees and employers. By the very nature of employment, employers have less need for a particular employee unlike the employee who cannot afford to be unemployed.
Num Pages: 67-75 Place: Indiana, United States
Keywords: Business And Economics; Compensation; Competition; Corporate culture; Emotions; Employees; Employers; Employment; Employment security; Empowerment; Games; Handbooks; Happiness; Job satisfaction; Personal computers; Physiology; Software; Stress; Success; Work environment; Workers; dept.mgt; peer-reviewed

Handbook on household hazardous waste - Cabaniss, Amy (Bernan, 2018)
Household hazardous waste (HHW) is a topic that affects every individual and community given the nearly universal use, storage, and disposal of chemical consumer products. Yet many communities lack the basic information, guidance, and planning support for HHW collection and management so that struggles (e.g., to gain politicians’ and residents’ support, host a collection, build a facility, affect behavior change, and encourage extended producer responsibility) continue on a regular basis. This book is for professionals, students, government officials and others interested in HHW and accommodating the increasing societal demand for this disposal option. In the evolving field of HHW collection and management, this book: provides an unparalleled, comprehensive look at household hazardous wasteis a must-have for anyone interested in the solid waste management field, whether novice or experienced, because of the valuable overview and specifics it provides for addressing the ubiquitous issue of HHWoffers perspectives based on many collective years of experts’ accrued insightthe chapters are written by leading practitioners and visionariesis packed with useful information on many aspects of HHW including its definition, mechanisms for collection and creative collection options, tools for behavior change, and product stewardshipoffers an extensive resource list for more information. Much has changed in 10 years since the first edition appeared, and each chapter in the Handbook on Household Hazardous Waste, Second Edition, is updated to reflect changes and advances in the field of HHW collection and management. This includes updated appendices and the extensive resource list.
Keywords: dept.mgt

Kinship ties and employee theft perceptions in family-owned businesses - O'Brien, Kimberly E; Minjock, Robert; Colarelli, Stephen M; Yang, Chulguen (European Management Journal, 2018)
Family business research typically views family firms using the frameworks developed for non-family businesses (e.g., agency theory, institutional theory). Thus, using an evolutionary perspective on family may help address gaps in the family business literature, particularly regarding deviance. In the current study, we use kin selection theory to predict that family members receive preferential treatment and this history of privileges can create entitlement and lead genetically-related employees to misuse company resources. Using an experimental vignette methodology and data from 161 people recruited from an online panel, we found that the participants' purported genetic relatedness to the owner of a business increased their theft intentions and decreased their expected severity of sanctions and likelihood of being reported. Biological sex moderated the relationships between genetic relatedness and theft intentions, as well as between expectations of punishment and theft intentions. Specifically, when females expected higher severity of sanctions or likelihood of whistleblowing, they were less likely to report theft intentions, compared to males. The results of this study suggest that family business owners should protect against theft by all employees, including genetic relatives. Future research using field samples would help provide context for these findings. (C) 2017 Elsevier Ltd. All rights reserved.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-210-309-412-58X tex.type: [object Object]
Keywords: Counterproductive behaviors; Evolutionary theory; Family business; Kinship; Lab experiment; Nepotism; Theft; dept.mgt; peer-reviewed

Making sense of mindfulness in management education - Yang, Charlie (Developing a Sustainability Mindset in Management Education, 2018)
Keywords: dept.mgt

Pay openness movement: Is it merited? Does it influence more desirable employee outcomes than pay secrecy? - Marasi, Shelly; Wall, Alison; Bennett, Rebecca J. (Organization Management Journal, 2018)
Organizations are currently moving toward increased pay openness in the workplace; thus, it is important to determine the influence pay communication practices (pay secrecy and pay openness) have on employee outcomes and whether the increase in pay openness is merited and more beneficial for organizations. The purpose of this article is to analyze pay communication’s influence on workplace deviance and organizational citizenship behaviors (OCBs). Specifically, pay secrecy practices are hypothesized to influence employees to engage in less OCBs and more workplace deviance. Informational justice and distributive justice perceptions are included as mediators. Pay secrecy leads to greater workplace deviance as well as less OCBs and justice perceptions and thus, inferring the pay openness movement is merited. A Pay Communication scale was developed and validated for this study. Practical implications, limitations, and future research directions are provided. © 2018 Eastern Academy of Management.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-494-664-059-042, pop00257 tex.type: [object Object]
Keywords: dept.mgt; distributive justice; informational justice; organizational citizenship behaviors; pay communication; pay openness; pay secrecy; peer-reviewed; workplace deviance

A Study on Cloud Computing Adoption Within Small and Mid-Size Businesses (smbs) - Richardson, Anthony; Mate, Geoffrey (International Journal of Interdisciplinary Research, 2018)
A growing number of organizations have difficulty scaling-up their IT infrastructure to handle their growing needs and increased resource demands. Digital Technology Platforms (DTPs) have been identified by Gartner, Inc. as one of the top 10 strategic technology trends of 2017. While DTPs may be mainstream and easily adopted by large enterprise-sized organizations, there is an opportunity for such platforms within Small and Mid-Size Businesses (SMBs). The bottom line is that computing and server hardware is expensive for SMBs. Furthermore, it may be difficult for SMBs to assess and price the labor and resources needed for a company to have acceptable performance while controlling costs. The purpose of this paper is to examine how cloud computing technologies are adopted by SMBs and the respective drivers associated with costs and capability that may reduce costs for an organization. This paper explores how four variables – Robust Capability, Limited Capability, Cost Constraint, and Resource Abundance interact to impact the adoption of DTPs within SMBs. Adopters of DTPs are classified as Efficient, Proactive, Resistive, and Reactive. With respect to adoption efficacy, a model is proposed for assessing the capability and resource readiness as correlated to SMB adoption of DTPs. A study of 12 SMBs and the implementations of DTPs is presented and posited with the proposed adoption model. Due to the extensive investments required in procuring infrastructure services –adoption enablement is imperative for SMB-sized organizations to realize a return on investment. Implications are discussed.
Keywords: dept.bis; dept.mgt; peer-reviewed; ⛔ No DOI found

Bullying in the workplace: The great balancing act of victim rights and organizational policies - Wall, Alison E.; Smith, Robert A.; Nodoushani, Omid (Journal of Competitiveness Studies, 2018)
Bullying in the workplace is considered a growing epidemic and organizations are struggling to ensure appropriate responses and protocol as there is currently no individual statutory remedy. This paper provides a synthesis of current research regarding workplace bullying, legal policies, efforts to promote remedial legislation and organizational responsibility and outcomes. Workplace bullying is addressed from several perspectives including organizational consequences, characteristics of both victims and perpetrators, the current state of legislation and best practices for organizational policy. The paper also provides a discussion of developing issues related to increased technology and social media usage.
Keywords: BULLYING in the workplace; CYBERBULLYING; VICTIMS of bullying; VIOLENCE in the workplace; WORK environment; dept.mgt; peer-reviewed; ⛔ No DOI found

Business schools, brand innovation and archetypal tradeoffs - Page Jr, Robert A.; Falk, Louis K. (Quarterly Review of Business Disciplines, 2018)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

How do humans interact with chatbots?: an analysis of transcripts - Park, Mina; Aiken, Milam; Salvador, Laura (International Journal of Management and Information Technology, 2018)
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/137-012-207-389-604 tex.type: [object Object]
Keywords: dept.bis; dept.mgt; peer-reviewed

More than a decade later: Arational decision cycles in post-Hurricane Katrina disaster management - Smith Jr, Robert A.; Page Jr, Robert A.; Badr, Kauther S. (Quarterly Review of Business Disciplines, 2018)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Personality testing by employers: Balancing the need for qualified workers with individual rights - Smith, Robert A.; Badr, Kauther S.; Wall, Alison E. (Competition forum, 2018)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Corporate slavery: Does it still exist? - Wall, A.; Smith, R.; Nodoushani, O. (Competition Forum, 2018)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found